Pretreatment of lignocellulosic materials by deep eutectic solvents for enhanced enzymatic hydrolysis - Zulkefli, Syarilaida (2015)
The potential of deep eutectic solvent (DES) for the process of oil palm biomass and cellulose conversion into glucose was investigated. DES has been studied extensively in various fields such as organic synthesis, biocatalysis, dissolution, electrochemistry and extraction process. Owing to its cheap and ‘green’ properties, we are interested in exploring the potential of DES for biomass processing. In order to achieve optimized glucose conversion via enzymatic hydrolysis, biomass must undergo pretreatment in order to break down the structure and this can enhance the access of cellulase to cellulose matrix which usually preferred amorphous or unorganized cellulose structure. Herein, choline chloride:glycerol (ChCl:Gly), choline chloride:ethylene glycol (ChCl:EG), ethylammonium chloride:glycerol (EAC:Gly), ethylammonium chloride:ethylene glycol (EAC:EG) and choline chloride:urea (ChCl:U) with 1:2 molar ratio for all DESs were used as solvent for pretreatment of oil palm biomass and cellulose. The dissolution process was done by heating and stirring 5% (w/w) oil palm biomasses which were trunk (OPT), frond (OPF) and empty fruit bunch (EFB) in ChCl:Gly, ChCl:EG, EAC:Gly, EAC:EG and ChCl:U at 100 °C for 48 h and cellulose for 24 h at the same temperature. The chemical composition for pretreated oil palm biomass was investigated and it was found that EAC:EG gave major removal of hemicellulose in OPT, while significant lignin reduction was shown in all DESs for OPT. The highest percentage of dissolution for oil palm biomass was recorded by OPT pretreated in EAC:EG with 55.6% while the lowest dissolution recorded by OPF pretreated in ChCl:Gly with only 20%. The highest percentage of dissolution for cellulose was also recorded when pretreated in EAC:EG with 22.9% while ChCl:EG gives the lowest dissolution with only 7.6%. The regenerated or pretreated oil palm biomass was recovered by adding distilled water/ethanol to the pretreated sample. Recovered pretreated samples were analysed by optical microscopy for physical structure study. The result shows that EAC:EG provides better media for dissolution process as the solvent produced more small fragments which indicates that dissolution occurred for oil palm biomass and cellulose. From FTIR analysis, EAC:EG was recorded to be the best solvent for disruption of hydroxyl group in the biomass material while ChCl:U recorded the best solvent in removing lignin for OPT.The screening of parameter study was carried out for enzymatic hydrolysis in order to determine the optimum conversion for the substrate pretreated in DES. Study of few crucial factors affecting the reaction rate such as hydrolysis media, enzyme loading and substrate concentration was conducted. The highest glucose release among pretreated oil palm biomass was when hydrolysing OPT pretreated in EAC:EG with 60% conversion. Cellulose hydrolysis recorded high amount of glucose release within range of 77-95% conversion. The optimisation study was carried out by using OPT pretreated in EAC:EG, not the cellulose because it considered to already achieved high conversion rate. The optimum condition was obtained by using 15 mg/ml as substrate concentration, 50 FPU/g and 100 CBU/mL as enzyme loading for Celluclast 1.5 L and Novozyme 188 respectively at 50 °C for 24 h with 73.5% glucose conversion.